Genotoxicants target distinct molecular networks in neonatal neurons. - Kisby GE; Olivas A; Standley M; Lu X; Pattee P; O'Malley J; Li X; Muniz J; Nagalla SR (Environmental Health Perspectives, 2006)
BACKGROUND: Exposure of the brain to environmental agents during critical periods of neuronal development is considered a key factor underlying many neurologic disorders. OBJECTIVES: In this study we examined the influence of genotoxicants on cerebellar function during early development by measuring global gene expression changes. METHODS: We measured global gene expression in immature cerebellar neurons (i.e., granule cells) after treatment with two distinct alkylating agents, methylazoxymethanol (MAM) and nitrogen mustard (HN2). Granule cell cultures were treated for 24 hr with MAM (10-1,000 microM) or HN2 (0.1-20 microM) and examined for cell viability, DNA damage, and markers of apoptosis. RESULTS: Neuronal viability was significantly reduced (p < 0.01) at concentrations > 500 microM for MAM and > 1.0 microM for HN2; this correlated with an increase in both DNA damage and markers of apoptosis. Neuronal cultures treated with sublethal concentrations of MAM (100 microM) or HN2 (1.0 microM) were then examined for gene expression using large-scale mouse cDNA microarrays (27,648). Gene expression results revealed that a) global gene expression was predominantly up-regulated by both genotoxicants; b) the number of down-regulated genes was approximately 3-fold greater for HN2 than for MAM; and c) distinct classes of molecules were influenced by MAM (i.e, neuronal differentiation, the stress and immune response, and signal transduction) and HN2 (i.e, protein synthesis and apoptosis). CONCLUSIONS: These studies demonstrate that individual genotoxicants induce distinct gene expression signatures. Further study of these molecular networks may explain the variable response of the developing brain to different types of environmental genotoxicants.